Implementasi Tata Kelola Pemerintahan dalam Penanggulangan Kekerasan terhadap Anak di Kabupaten Bintan - A. Karim, Zamzami; Mukhlis, Suhardi; Usman Siam, Nurbaiti; Awaliah, Fanda (STISIPOL Raja Haji, 2023)
Cases of violence against children in the Bintan Regency area since 2016 until now have continued to increase, various cases of violence that occurred against children in Bintan Regency such as cases of obscenity, sexual harassment, theft, TIP, traffic accidents, attempted suicide, neglect of children, and child trafficking. This shows that there are problems in good local government governance (Good Governance). This study aims to determine governance in overcoming violence against children in bintan district. Through literature study using descriptive analytic method, through data collection by conducting in-depth interviews and observations. The results of this study are that governance in overcoming violence against children in Bintan Regency has been implemented, but it is still not optimal. This is due to the inhibiting factor from the community to report cases of violence they or their families experience, namely the feeling of